Rosacea and Demodicosis: Little-known Diagnostic Signs and Symptoms - Fabienne M.N. Forton; Viviane De Maertelaer (Medical Journals Sweden, 2018)
Papulopustular rosacea and demodicosis are characterized by non-specific symptoms, which can make clinical diagnosis difficult. This retrospective study of 844 patients assessed the diagnostic importance of clinical signs and symptoms that are poorly recognized as being associated with these conditions. In addition to well-known signs (vascular signs (present in 80% of patients), papules (39%), pustules (22%) and ocular involvement (21%)), other signs and symptoms (discreet follicular scales (93%), scalp symptoms (pruritus, dandruff or folliculitis; 38%) and pruritus (15%)) may also suggest a diagnosis not only of demodicosis, but also of papulopustular rosacea. Facial Demodex densities (measured by 2 consecutive standardized skin biopsies) were higher when ocular or scalp involvement was present, suggesting more advanced disease, but further investigations are needed to confirm this hypothesis. Recognition of these clinical signs and symptoms should encourage dermatologists to perform a Demodex density test, thus enabling appropriate diagnosis to be made.